Cytotoxicity and antimitotic activity of Rhinella schneideri and Rhinella marina venoms. (5th October 2019) - Abdelfatah, Sara; Lu, Xiaohua; Schmeda-Hirschmann, Guillermo; Efferth, Thomas
Abstract: Ethnopharmacological relevance: Rhinella schneideri and Rhinella marina are toad venoms distributed in different parts of the world, including Brazil, Columbia and amazon. Venoms extracted from different species have many clinical applications such as antimicrobial cardiotonics and treatment of cancer. Aim of the study; In this study, we aim to investigate the effect of venoms extracted from R. schneideri and R. marina on cancer cells and verify possible mechanism of action. Material and method: Cytotoxicity analyses was performed using the resazurin reduction assay, where different concentrations of venoms were tested against sensitive CCRF-CEM and P-gp overexpressing ADR/CEM5000 leukemia cells. Programmed cell death was investigated using the flow cytometric annexin V/propidium iodide apoptosis assay. Furthermore, we analyzed flow cytometric cell cycle analyses of CCRF-CEM cells. Effect on tubulin formation was tested using molecular docking and fluorescence microscopy of U2OS-GFP-α-tubulin osteosarcoma cells treated for 24 h with venoms. Results: Cytotoxicity assays revealed a strong activity towards wild-type CCRF-CEM cells (IC50 values of 0.202 ± 0.005 μg/ml and 0.18 ± 0.007 μg/ml for R. schneideri and R. marina, respectively) and multidrug-resistant CEM/ADR5000 cells (IC50 0.403 ± 0.084 μg/ml and 0.32 ± 0.077 μg/ml for R. schneideri and R. marina, respectively). The venoms induced apoptosis as major mechanism of cell death. The venoms induced strong G2/M cell arrest in CCRF-CEM cells. We suggested tubulin as a major target for the venoms. In silico molecular docking of the major constituents of the venoms, i.e. bufalin, marinobufagin, telocinbufagin, hellebrigenin, showed strong binding affinities to tubulin. This result was verified in vitro . The venoms dysregulated microtubule arrangement of U2OS cells expressing GFP-labeled tubulin. Toxicity predictions by QSAR methodology highlighted the toxic features of bufadienolides. Conclusion: Our study demonstrated the importance of toad venoms as source of cytotoxic compounds that may serve as lead compounds for the development of novel anticancer drugs. Graphical abstract: Image 1